Perception and Attitude of Turkish Gastroenterologists Toward Obesity: A Nationwide Survey Conducted by the Obesity Study Group of the Turkish Gastroenterology Association - Tahtacı, Mustafa; Yıldırım, Emre; Üçbilek, Enver; Şen, İlker; Bilican, Gülden; Şimşek, Zahide; Gümüş, Süheyla Ayça; Aladağ, Murat; Kıyıcı, Murat; Cindoruk, Mehmet; Karakan, Tarkan (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Gastroenterologists have an important role in the treatment and management of comorbidities related to obesity. Assessment of gastroenterologists perception and attitude toward obesity was aimed in this study. Materials and Methods: Survey questions were determined for the study. An online questionnaire was prepared afterward. Participants were invited via e-mail by providing them with information about the study. It was ensured that those who accepted the study could access the questionnaire form with the relevant link. Participants who answered all questions were included in the study. Results: Totally 117 gastroenterologists were included in the study. The proportion of gastroenterologists who thought that obesity complicates the management of gastroenterological diseases and those who thought obesity as a factor that negatively affects the prognosis of gastroenterological diseases was determined as 88.9% and 95.7%, respectively. Among the obese patients, the proportion of those who applied diet therapy, exercise, pharmacotherapy, and endoscopic methods was 94%, 91.5%, 35%, and 37.6%, respectively. The rates of intragastric balloon therapy and intragastric botulinum toxin A injection were 30% and 21.4%, respectively. The proportion of those who agreed that obese patients lost a significant amount of weight with the treatment methods applied was 47.2%. The proportion of participants who agreed that long-term maintenance of weight loss was impossible for most obese patients was 59.8%. Conclusion: To our knowledge, this is the first study that evaluates the perception and attitude of gastroenterologists toward obesity. Our study results show that gastroenterologists think that obesity is a chronic disease and that gastroenterologists should be involved in management of obesity. Cite this article as: Tahtacı M, Yıldırım E, Ç bilek E, et al. Perception and attitude of Turkish gastroenterologists toward obesity: A nationwide survey conducted by the Obesity Study Group of the Turkish Gastroenterology Association. Turk J Gastroenterol. 2024;35(3):161-167.